2012
DOI: 10.1016/j.jep.2012.08.030
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil of Croton zehntneri and trans-anethole improves cutaneous wound healing

Abstract: Our data indicate that EOCz exerts significant wound healing activity, demonstrating its relevant therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…We studied not only the combination of FEO with MUP, but also the combination of FEO main component – t A with MUP which, according to available data, improves cutaneous wound healing. This provides data on its oral LD 50 values between 1.8–5.0 g for mice, rats and guinea pigs [26, 27]. It can be concluded that antimicrobial activity of FEO compared with t A is determined by more than one particular component, and depends on the synergistic activities of different oil constituents.…”
Section: Discussionmentioning
confidence: 99%
“…We studied not only the combination of FEO with MUP, but also the combination of FEO main component – t A with MUP which, according to available data, improves cutaneous wound healing. This provides data on its oral LD 50 values between 1.8–5.0 g for mice, rats and guinea pigs [26, 27]. It can be concluded that antimicrobial activity of FEO compared with t A is determined by more than one particular component, and depends on the synergistic activities of different oil constituents.…”
Section: Discussionmentioning
confidence: 99%
“…This new local anesthetic effect adds to the list of other pharmacological actions of estragole, such as antimicrobial (7), antioxidant (8), anti-edematogenic, and anti-inflammatory (13) effects, and places this substance as a candidate for therapeutic usefulness to treat ulcerations (infected or not), for example, and similar illnesses. In addition to these activities, one can consider that anethole, with a molecular structure very similar to estragole, has been documented to have procicatrizing activity (36). This prospect also increases when one takes into consideration recent studies showing that long-lasting per os administration of 37.5 mg/kg estragole showed no toxic effects (37), suggesting that extracts having estragole as the principal constituent, like fennel seed extract, have anticancer (for certain types of cancer) and antioxidant activities, and radical scavenging potential (38).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus have been used in traditional medicine to treat a wide range of disorders, including malaria, inflammation, diabetes and cancer [2]. The biological properties of various Croton species have been investigated in laboratory studies involving murine models [3,4,5,6,7,8,9,10]. The chemical composition of Croton is somewhat diverse, although alkaloids [11,12], diterpenoids [13,14] and volatile oils comprising mono- and sesquiterpenoids [15,16,17,18], have been commonly reported.…”
Section: Introductionmentioning
confidence: 99%